Islāmic counselling and psychotherapy: an introduction to theory and practice - Rassool, G. Hussein (Routledge, 2025)
"Islāmic Counselling and Psychotherapy: An Introduction to Theory and Practice provides a foundation level knowledge of and perspective on the fundamental principles and practices of counselling and psychotherapy from an Islāmic perspective. This groundbreaking practical framework incorporates Islāmic spirituality, religion, and cultural contexts into the therapeutic process. It makes the case that authentic Islāmic spirituality, based on submission to God, forms the cornerstone of good mental health. The book's foundation focuses on the therapist's role and ethical considerations specific to Islāmic psychotherapy. It explores the integration of Qur'ânic teachings and hādīths and delves into dream interpretation and the clinical applications of the Siraat Al-Islāmic Psychotherapy Practice Model. This thoroughly revised new edition also highlights advances and developments in scholarship and evidence-based practices, and introduces postmodern psychotherapy approaches like narrative and hope therapy. This text provides a clear understanding of the nature, scope and process of Islāmic psychotherapy for Islāmic practitioners or clinicians working with Muslim clients"--